Determination of size-independent specific fracture energy and corresponding stress vs crack width relation for various concretes - Muthuraj, M.P.; Nithyapriya, K. (Journal of Structural Engineering, 2025)
The size independent specific fracture energy and the corresponding tension softening relation σ (w) between the residual stress carrying capacity σ and the crack opening w in the fracture process zone ahead of a real crack are the important properties essentially required in the analysis of the mechanical behaviour of cracked concrete structures. The present study deals with the estimation of size independent specific fracture energy and the corresponding bi-linear tension softening relation for various concretes. RILEM work of fracture method with tail correction for the load – deflection plot has been employed to estimate the size independent fracture energy. Bi-linear tension softening relation corresponding to size independent fracture energy has been constructed in an inverse manner based on the concept of a non-linear hinge from the load-crack mouth opening plots of notched three-point bend beams.